Analisis Kesalahan Keterampilan Menulis Permulaan pada Siswa Kelas II di SD Negeri Plaosan 1 - Nadhira Audrey Emilia; Galih Kusumo (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2024)
This research aims to analyze the writing errors of second-grade students to help them improve before advancing to the next grade level in third grade. This study is a descriptive qualitative research. The data collection techniques used are observation and documentation study. The results of the research show that: 1) exceeding the boundary lines in notebooks is experienced by 5 students, 2) writing each word in a sentence unevenly is experienced by 14 students, 3) significant differences in the size of each letter are experienced by 7 students, 4) excessive spacing between words or sentences occurs in 1 student, 5) omission of words in a sentence is experienced by 5 students, 6) omission of letters in written words occurs in 9 students, 7) writing incomplete home addresses is experienced by 25 students, 8) incorrectly copying sentences from examples occurs in 1 student, 9) inconsistent use of capital and lowercase letters is experienced by 11 students, 10) not placing capital letters at the beginning of sentences is observed in 16 students, 11) incorrect use of punctuation is experienced by 12 students, 12) unclear legibility is experienced by 4 students. Therefore, there are still second-grade students who have initial writing errors.